Pembuatan Media Belajar English For Ecotourism Untuk Masyarakat Hinterland - Satriya Bayu Aji; Condra Antoni; Yosi Handayani; Arta Uly Siahaan; Eka Mutia Lubis; Maryani Septiana; Afdhol Dzikri; Dwi Ely Kurniawan; Desi Ratna Sari; Tian Havwini; Firmal Firmal; Nur Imma Aulia Astori (Pusat P2M Politeknik Negeri Batam, 2020)
The English communication skill of people in Pasir Panjang in the context of tourism and trade is still inadequate. To support trade activities, English communication skill is required, especially for those who run business, such as traders as well as other service providers. For this reason, this community service activity was carried out in the form of training. The materials consists of an introduction to vocabulary and idiom commonly found in the context of tourism and trade activities. In this training, several learning media was used to increase participants' interest in learning. Through the delivery of English communication training, it is hoped that communication in English related to tourism and trade can take place more effectively. For the people of Pasir Panjang, an increased confidence level is another benefit that can be acquired through mastery of English, which is considered to hold high prestige by most Indonesians. From the activity that has been carried out, it can be concluded that the media are effective in the delivery of the material. This is evident from the opinion of most participants stating the media are interesting and helps them in learning English.